DAMPAK BENCANA BANJIR SUNGAI TEHADAP KESEHATAN MASYARAKAT DI KABUPATEN NIAS UTARA (Studi kasus Sungai Muzei dan Sungai Sowu) - HAREFA, TOROTODO ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Flood in Nias Utara district, especially in Muzei Village, lahawa timur sub district, and Hilimbosi vilage, Sitelu ori sub district becomes a problem that rising every year. the impacts of flooding are, disease, inundation in housing residents, housing damages, ricefield damage and livestock die, and water sources damage in the villages so many people consume drinking water in the river and well with bad q-q,ality. Knowing the impact of the floods ~o public health condition in Muzei Village, Lahewa Timur sub distric and Hilimbosi village, Sitolu ori sub district. the variables in this research are environmental sanitation and disease after flooding. data collection using indepth interview, observation and secondary data from the sub disrict office. based on the data analysis, it showed that the impact of the flooding in Muzei village, Lahewa Timur sub district and Hilimbosi village, Sitolu Ori sub district is the flooding prone area and disease. therefore, its need an alternative solution to overcome the problem.